Self-organized double-wall oxide nanotube layers on glass-forming Ti-Zr-Si(-Nb) alloys - Sopha, Hanna; Pohl, Darius; Damm, Christine; Hromádko, Luděk; Rellinghaus, Bernd; Gebert, Annett; Macák, Jan M. (Elsevier, 2016)
In this work, we report for the first time on the use of melt spun glass-forming alloys - Ti75Zr10Si15 (TZS) and Ti60Zr10Si15Nb15 (TZSN) - as substrates for the growth of anodic oxide nanotube layers. Upon their anodization in ethylene glycol based electrolytes, highly ordered nanotube layers were achieved. In comparison to TiO2 nanotube layers grown on Ti foils, under the same conditions for reference, smaller diameter nanotubes (~ 116 nm for TZS and ~ 90 nm for TZSN) and shorter nanotubes (~ 11.5 μm and ~ 6.5 μm for TZS and TZSN, respectively) were obtained for both amorphous alloys. Furthermore, TEM and STEM studies, coupled with EDX analysis, revealed a double-wall structure of the as-grown amorphous oxide nanotubes with Ti species being enriched in the inner wall, and Si species in the outer wall, whereby Zr and Nb species were homogeneously distributed.
Keywords: Nanotubes; Anodization; Self-organization; Alloys; TEM